Comparative Analysis of Space-Based Battery, Fuel Cell, and Conventional Propulsion System for General Cargo Ships Of Approximately 100 Meters - Axel Rafoth; Achmad Baidowi; Quito Abian Iqtarib (International Journal of Marine Engineering Innovation and Research, 2024)
This research aims to serve as a guidebook or framework for designing a general cargo ship, approximately 100 meters in length, by replacing the conventional diesel system with hydrogen and fuel cell technology. The reference vessel for this study is the general cargo ship with about 100m length operated in Baltic Sea. The results of this research provide the foundational calculations for designing a ship powered by hydrogen fuel cells, including the selection of hydrogen type, battery choice, and compliance with class standards. Additionally, the transformation of the ship's layout is a key outcome of this study. Based on the calculations, the ship, with a sailing duration of approximately three days, requires around 2800 kg of liquid hydrogen. This hydrogen supply can support 4 x 200 kW fuel cells and 5 x 70 kWh batteries. Ultimately, this allows for the design of a hydrogen-powered ship with an endurance of three days.